Test Of Courage Skills Class Iv Students' In Raising Opinions Through Language Game To Improve Learning Achievement Results - Usnita Usnita (Fakultas Sastra Universitas Ekasakti, 2018)
School is a place of formal education. All activities that occur within the school are directed and planned in such a way as to achieve a quality output. Quality output in education can be realized if supported by environmental components that work together and are responsible. Dirto Hadisusanto (2003: 157) states that education lasts a lifetime and is implemented within families, schools and communities, so that education is a shared responsibility between family, government and society. One indicator to know the level of quality of education conducted in schools is the achievement of student learning. Efforts to improve student achievement have been done by educational institutions either through the addition of learning facilities, curriculum improvement, teacher competency improvement, research, seminars and others. Implementation of class actions that have been implemented with rounds and based on observations, collect data and evaluate the results can be summarized as follows: 1) The language game method with fast quiz right, quiz figures and quiz Who He was able to engage students actively in the learning process, and grade 6 students of SDN 02 Teratak Teleng Sub District IV Nagari Bayang Utara Pesisir Selatan District Lesson Year 2015/2016 is very prominent. 2) The language game method is very effective to increase the courage of the students of class VI SDN 02 Teratak Teleng Sub District IV Nagari Bayang Utara Pesisir Selatan District Lesson Year 2015/2016 in expressing opinions. This can be seen from the results of each round which indicates an increase in student activity. From the first round the correct answer is 77.3%, while the punishment is 19.1%. 3) the ability of language game methods in increasing courage in expressing opinion very well, because it can be seen actively in teaching and learning process so that learning many with smooth and live.